Effects of Binahong (Anredera cordifolia (Tenore) Steenis) Extracts on the Levels of Malondialdehyde (MDA) in Cataract Goat Lenses - Feriyani Feriyani; Hady Maulanza; Rodiah Rahmawaty Lubis; Ummu Balqis; Darmawi Darmawi (The Scientific World Journal)
Cataracts are one of the most causes of blindness in the world. Oxidative stress can form pathological conditions such as cataracts. This oxidative stress ability can be measured by the malondialdehyde (MDA) biomarker. Binahong leaves (Anredera cordifolia (Tenore) Steenis) are native plants from Indonesia that are used to treat various diseases including cataract treatment. Binahong leaf (Anredera cordifolia (Tenore) Steenis) has a high amount of flavonoids and is rich in antioxidants that can be used to treat cataracts. Objective. The purpose of this study was to assess the effect of binahong leaf extract on the levels of MDA in a goat lens with cataract-induced material. Method. As many as possible, 40 goat eye lenses were divided into several groups, namely, group I normal lenses as controls (glucose 5.5 mM), group II lenses were cataract induced with glucose concentration of 55 mM, group III lenses with glucose 55 mM + binahong leaf extract (100 μg/ml), group IV lens with glucose 55 mM + binahong leaf extract (200 μg/ml), and group V lens with glucose 55 mM + quercetin (positive control). Biochemical parameters measured in the lens homogenate are malondialdehyde lens morphology in all groups’ observations and comparisons made. Results. The results of the study found that the lens group with the addition of binahong extract showed more results transparency compared to lens groups induced by glucose concentrations of 55 mM). This shows that the diabetic cataract group experienced high oxidative stress due to the accumulation of sorbitol compounds derived from glucose which caused turbidity in the goat eye lens and increased levels of lens MDA. Binahong levels at concentrations of 100 or 200 can inhibit MDA production. Conclusion. Binahong (Anredera cordifolia (Tenore) Steenis) extract has the ability to inhibit the production of MDA levels. In glucose-induced goat lenses, binahong extract and quercetin show antioxidant and anticataract properties.